2012
DOI: 10.1007/s13105-012-0169-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperoxia exposure on metabolic markers and gene expression in 3T3-L1 adipocytes

Abstract: Adipose tissue often becomes poorly oxygenated in obese subjects. This feature may provide cellular mechanisms involving chronic inflammation processes such as the release of proinflammatory cytokines and macrophage infiltration. In this context, the purpose of the present study was to determine whether a hyperoxia exposure on mature adipocytes may influence the expression of some adipokines and involve favorable changes in specific metabolic variables. 3T3-L1 adipocytes (14 days differentiated) were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 70 publications
5
24
1
Order By: Relevance
“…However, as oxygen is known to be toxic in high concentrations, this treatment may not be healthy in terms of circulatory and metabolic function. Hyperoxia is known to decrease adipose cell viability, increase both intra- and extracellular oxidative stress, provoke inflammation, and decrease glucose uptake of adipocytes (69). Hence, based on this information on hyperoxia and reviewed knowledge regarding hypoxia, it is concluded that there is a delicate balance of healthy oxygen supply and demand in adipose tissue that determines its overall function.…”
Section: Hypoxia As a Treatment Of Obesity And Impaired Adipose Tissumentioning
confidence: 99%
“…However, as oxygen is known to be toxic in high concentrations, this treatment may not be healthy in terms of circulatory and metabolic function. Hyperoxia is known to decrease adipose cell viability, increase both intra- and extracellular oxidative stress, provoke inflammation, and decrease glucose uptake of adipocytes (69). Hence, based on this information on hyperoxia and reviewed knowledge regarding hypoxia, it is concluded that there is a delicate balance of healthy oxygen supply and demand in adipose tissue that determines its overall function.…”
Section: Hypoxia As a Treatment Of Obesity And Impaired Adipose Tissumentioning
confidence: 99%
“…Most of these studies have demonstrated that extremely low PO 2 induces a pro-inflammatory response in 3T3-L1 adipocytes ( 18 , 27 31 ), human adipocytes ( 32 ), stromal–vascular cells ( 33 , 34 ), and macrophages ( 18 , 35 ), although conflicting results have also been reported ( 36 , 37 ). On the other hand, 95% O 2 also increased pro-inflammatory gene expression and reactive oxygen species (ROS) content, and reduced glucose uptake in 3T3-L1 adipocytes ( 38 ). These in vitro studies should be interpreted with some caution, because these cells were acutely exposed to extremely low (or high) PO 2 .…”
Section: Consequences Of Altered Oxygen Tension: a Matter Of Severitymentioning
confidence: 99%
“…This is the case of obesity, where established hypoxia occurs at the adipose tissue level (due to adipose tissue expansion in cell number and size) causing several alterations, such as macrophage infiltration and generation of ROS, that lead to a pro-inflammatory state within that tissue (103)(104)(105)(106). Today, strong scientific evidence based on cell culture, animal, and human studies support that hypoxia plays a fundamental role in the initiation and development of obesity (107)(108)(109).…”
Section: H) Hypoxiamentioning
confidence: 99%